Do Time in Child Care and Peer Group Exposure Predict Poor Socioemotional Adjustment in Norway?. Issue 5 (5th March 2013) - Solheim, Elisabet; Wichstrøm, Lars; Belsky, Jay; Berg‐Nielsen, Turid Suzanne
Abstract : Extensive exposure to nonparental child care during the first 4.5 years of life has been demonstrated in some American studies to negatively affect children's socioemotional functioning. Data from 935 preschool children who averaged 54.9 ( SD  = 3.0) months of age, from Trondheim, Norway were used to examine whether such negative effects, would emerge in Norway, a country with a different child‐care system. The children's externalizing problems and social competence were unrelated to their child‐care experience. More time spent in child care during the first 4.5 years of life and experiencing peer groups of < 16 or > 18 children predicted greater caregiver–child conflict. The effect sizes were small. The results are discussed in terms of cross‐national child‐care differences.